Advancing Entrepreneurship Education: An Integrated Approach to Empowering Future Innovators - Birgit Oberer; Alptekin Erkollar (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Entrepreneurship plays a central role in driving economic growth and fostering innovation worldwide. As the business landscape becomes increasingly dynamic and competitive, the need for effective entrepreneurship education has never been more critical. This paper presents an integrated framework for entrepreneurship education that addresses the limitations of traditional approaches and aims to equip aspiring entrepreneurs with the necessary mindset, skills, and ecosystem engagement to thrive in the ever-evolving entrepreneurial landscape. The framework focuses on mindset development, skills acquisition, and ecosystem engagement as essential pillars for empowering and nurturing future innovators, contributing to the advancement of entrepreneurship education and the cultivation of a new generation of successful entrepreneurs and innovators.